Historical dynamics of marginal populations at the leading edge of a temperate species in the boreal‐temperate ecotone - Pierre‐Yves Mondou Laperrière; Todor S. Minchev; Pierre Grondin; Martin Lavoie; Guillaume de Lafontaine (Ecosphere)
Abstract Marginal populations of temperate species at the leading edge of their range will likely play a key role at the boreal‐temperate ecotone (BTE) in the face of climate changes. In eastern North America, red maple (Acer rubrum L.) is the most abundant temperate tree species encroaching into the boreal forest. In order to provide useful insights about possible responses to climate change and anticipate the formation of new assemblages, this study relies on long‐term Holocene data from forest soil wood macrofossils (charcoal and ligneous remains) and contemporary stand analyses to assess the postglacial origin and modern‐day dynamics of red maple at its leading edge within the BTE. We sampled the soils of eight marginal red maple stands. Macroscopic charcoal particles and ligneous remains were identified using microanatomical characteristics. Macrofossils of temperate tree species were radiocarbon dated to reconstruct their long‐term stand‐scale history. Contemporary dynamics (<200 years) were assessed by analyzing tree size structure of all stems within 400 m2 plots, minimal stand age from tree‐ring dating, as well as the recent occurrence of fire and logging from published ecoforest data. White pine (Pinus strobus L.), the only other temperate tree species that was identified, was present 6500–4000 years ago, during the mid‐Holocene thermal maximum but decreased during the cooler and fire‐prone late‐Holocene Neoglacial (4000 years ago to present). By contrast, red maple was found at its current northern limit since the last 4000 years. Modern‐day marginal red maple stands are self‐regenerating populations that established following a recent stand‐replacing disturbance (wildfire or clearcut). The present‐day increase of anthropogenic disturbances within the BTE could mirror the Neoglacial increase in fire activity that fostered red maple during the Holocene. We thus predict that red maple is poised to increase in abundance within the BTE, which should facilitate the northward establishment of other temperate deciduous species into the boreal forest prompted by the new conditions brought about by anthropogenic or climate change‐induced disturbances.